First virtual uro-oncology meeting during the COVID-19 pandemic: 10th Online Eurasian Uro-oncology Congress - Çulpan, Meftun; Yıldırım, Asıf; Canda, Abdullah Erdem; Çil, Timuçin; Gümüş, Mahmut; Albayrak, Selami (Eurasian Urooncology Association, 2021)
Objective: COVID-19 has rapidly spread and has become a pandemic by affecting the whole world. During this period, many scientific congresses and educational meetings had to be canceled because of preventive measures. In this report, we aimed to share our first live virtual congress experience, described its process of transformation from face to face to virtual congress and report the attendees and speakers’ satisfaction. Material and Methods: Eurasian Uro-oncological Association (EUA) decided to organize the 10th Eurasian Uro-oncology congress in June 2020 at Göbeklitepe, Şanlıurfa in Turkey. However, due to the COVID-19 pandemic, the organizing committee decided to organize the first virtual scientific congress in Turkey. The planned duration of the congress was reduced from 4 days to 2 days and each speaker was planned to give the speech online during the presentation via ZOOM program (San Jose, CA). Results: A total of 704 persons registered to the congress. It was the highest number of participants among whole congresses that was organized by EUA. In this congress, there were 199 oral presentations, 25 interactive e-posters and 12 video presentations. During the congress, each participant attended the congress for an average of 387 minutes. It was identified that the majority of the participants were quite satisfied with the program offered. In general, participants were fairly satisfied with the quality of images and sound, chat functionality, questions & answers section and technical support In this report, we shared the outcomes of our first virtual congress experience in Turkey through the 10th Eurasian Uro-oncology Congress. Today, virtual congresses have become the “new normal” and offer cheaper events with larger participation in the comfort of home.

Amaç: COVİD-19 hızlıca yayılarak kısa sürede tüm dünyayı etkileyen bir pandemi haline gelmiş ve bu süreçte koruyucu önlemler nedeniyle birçok bilimsel kongre ve eğitim toplantısı iptal edilmek zorunda kalınmıştır. Bu çalışmada, ilk canlı, online kongre deneyimimizi paylaşmayı, yüz yüze geleneksel kongreden online kongreye geçiş sürecini anlatmayı ve katılımcı ve konuşmacıların memnuniyetlerini ortaya koymayı amaçladık. Gereç ve Yöntemler: Avrasya Üroonkoloji Derneği (AÜD), 10. Avrasya Üroonkoloji Kongresi’ni Haziran 2020’de Şanlıurfa-Göbeklitepe, Türkiye’de düzenlemeye karar vermişti. Ancak organizasyon komitesi COVİD-19 pandemisi nedeniyle Türkiye’deki ilk online kongreyi düzenlemeye karar verdi. Planlanan kongre süresi 4 günden 2 güne düşürüldü ve her konuşmacının sunumlarını ZOOM programı (San Jose, CA) üzerinden yapmaları planlandı. Bulgular: Toplam 704 kişi kongreye kayıt yaptırdı. Bu sayı ile AÜD tarafından düzenlenen tüm kongreler arasında en fazla katılımcı sayısına sahip kongre bu kongre oldu. Kongrede 199 sözlü sunum, 25 interaktif e-poster ve 12 video sunumu yer aldı. Kongre süresince her katılımcı ortalama 387 dakika kongreye katıldı. Katılımcıların çoğunluğunun sunulan programdan oldukça memnun olduğu tespit edildi. Katılımcıların genel olarak görüntü ve ses kalitesinden, sohbet fonksiyonundan, soru-cevap bölümünden ve teknik destekten oldukça memnun olduğu saptandı. Sonuç: Bu makalede, Türkiye’deki ilk online kongre deneyimimizin sonuçlarını 10. Avrasya Üroonkoloji Kongresi ile sunduk. Günümüzde online kongreler “yeni normal” haline gelmiş durumdadır ve ev konforunda daha fazla katılımcı ile daha az maliyetli etkinlikler sunmaktadır.
COVİD-19 pandemisi döneminde ilk online üroonkoloji kongresi: 10. Online Avrasya Üroonkoloji Kongresi
Keywords: COVID-19; Congress; Virtual; Pandemic; Online; COVID-19; Kongre; Sanal; Pandemi; Online